Public Asset Utilization and Maintenance Strategy on Community Satisfaction: The Mediating Role of Service Quality at the Denpasar City Civil Registry Office - I Nyoman Ega Beerawa; Made Dwi Setyadhi Mustika (Journal of Business, Social and Technology, 2026)
Background: The commitment of the Head of Disdukcapil to continue optimizing various public services in Denpasar City, especially SIAK (Regional/City Information System), remains strong; however, the utilization of regional assets is still suboptimal (approximately 38%), and inconsistent maintenance strategies are among the factors contributing to fluctuations in these indices. This condition requires stronger asset governance to improve services. Objective: The purpose of this study is to analyze the influence of utilization and maintenance strategies on community satisfaction, with service quality as a mediating variable. Methods: This study uses an associative quantitative method with an explanatory research design. From a population of 20,169 service users, Slovin’s formula was used to determine a sample of 156 respondents. The PLS-SEM method was used in the data analysis to test the proposed hypotheses. Results: The results show that asset utilization and maintenance significantly influence service quality. Among these, the maintenance strategy was the most influential determinant (coefficient = 0.430). In addition, the relationship between asset governance and community satisfaction was partially mediated by service quality. Conclusion: There are critical periods in operating assets during which extra caution is required, as there may be factors not immediately visible that affect maintenance strategies. Moreover, it is important to strengthen cybersecurity to ensure the reliability of service assurance and, consequently, enhance community satisfaction.